The effect of ego-depletion on college students’ deceptive behavior: the role of anonymity and moral emotions - Ren, Lingxue; Ning, Meng; Chen, Zhihao; Zhang, Shaobo (Frontiers in Psychology, 2025)
ObjectiveThe present study aimed to investigate the effects of anonymity and moral emotions on college students’ deceptive behavior under different ego depletion conditions.MethodsIn Experiment 1, 120 college students were recruited and assigned to a 2 (ego depletion: high vs. low) × 2 (anonymity: anonymous vs. non-anonymous) between-participants design to examine the impact of anonymity on deceptive behavior under varying levels of ego depletion. In Experiment 2, 150 college students were recruited and assigned to a 2 (ego depletion: high vs. low) × 3 (moral emotions: positive vs. negative vs. neutral) between-participants design to investigate the effects of moral emotions on deceptive behavior under different ego depletion conditions.ResultsIn Experiment 1, results revealed a significant main effect of ego depletion: the high ego depletion group exhibited more deceptive behavior than the low ego depletion group, and their decision-making reaction times were shorter. The main effect of anonymity was also significant, with the anonymous group showing more deceptive behavior than the non-anonymous group. Moreover, a significant interaction effect was found; under high ego depletion conditions, the anonymous group exhibited greater deceptive behavior than the non-anonymous group (all p < 0.001). In Experiment 2, the main effect of moral emotions was significant: the positive moral emotion group exhibited less deceptive behavior than the negative moral emotion group, which in turn exhibited less deceptive behavior than the neutral emotion group. Additionally, a significant interaction effect was found, under high ego depletion conditions, the positive moral emotion group demonstrated less deceptive behavior than the negative moral emotion group, which, in turn, demonstrated less deceptive behavior than the neutral emotion group (all p < 0.001).ConclusionThe findings indicate that under high ego depletion conditions, college students engage in more deceptive behavior. Anonymity exacerbates the after-effects of ego depletion, leading to increased deception, whereas moral emotions help mitigate these after-effects and reduce deceptive behavior.